KNOWLEDGE AND PREDICTORS OF IMPLEMENTATION OF STANDARD PRECAUTIONS FOR INFECTION PREVENTION AND CONTROL AMONG HEALTH CARE PRACTITIONERS - AYOGU, Ebere E; ARAFATI, Aheebwa; EZEONWUMELU, Joseph Obiezu; EBOSIE, Jennifer; ISAH , Abdulmuminu; GORUNTLA, Narayana; UKWE, Chinwe (African Journal of Infectious Diseases (AJID), 2024)
Background: Infection prevention and control involve health care practitioners, who are saddled with the duty of ensuring implementation of standard preventive measures to prevent healthcare associated infections. Objectives: To assess the knowledge and predictors of implementation of standard precautions for infection prevention and control among health care practitioners (HCPs). Material and method: A questionnaire-based cross-sectional design was employed in assessing HCPs in Uganda in from April – October 2023. Data were analyzed using descriptive, Pearsons’ correlation, linear and binary logistic regression with the aid of SPSS Version 22 Results: Among the 222 healthcare practitioners assessed, 127 (57.2%) and 115 (51.8 %) had good knowledge and practice towards implementation of standard infection prevention and control precautions respectively. Chi square analysis indicated that age of healthcare practitioner (p=0.02; CI: 0.018 – 0.23), hospital unit of practice (p=0.003; CI: 0.002 – 0.004) and the type of facility where the health care practitioner works is significantly associated with their knowledge, while profession of the healthcare practitioner (p=0.002; CI: 0.001-0.003) and hospital unit of practice (p=0.002; CI: 0.001-0.003) were associated with implementation of the standard infection prevention and control precautions. Linear regression revealed knowledge is a significant predictor of good practice towards implementation of preventive measures (OR = 0.19; CI 0.102 – 0.272; p < 0.001). Conclusion. Healthcare practitioners had poor knowledge and practice towards infection prevention. Thus, emphasizing continuous education and training for all healthcare professionals about infection prevention and control interventions as well as strict adherence to proper infection prevention and control practices.